ANALISIS KONTRIBUSI DAN PELAPORAN PAJAK HOTEL DAN PAJAK AIR TANAH TERHADAP PENDAPATAN ASLI DAERAH KOTA MANADO - Ruung, Novianti Valentin; Ilat, Ventje; Wokas, Heince R. N. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
The Indonesian government imposed a policy of regional autonomy with the aim to facilitate local governments regulate local affairs indenpently.  Manado city is one of the areas that implement decentralization policy and requires a lot of funds to finance regional development. The biggest potential possessed Manado city in the financingof regional expenditures derived from local taxes and are expected to ptovide the largest contribution in PAD. This study aims to determain the amount of contribions hotel tax and groundwater tax and to analyze hotel tax and groundwater tax  the city of Manado. Methods of data analysis in this research is descriptive analysis. Based on the analysis the average  contrition colletion hotel and  groundwater tax city parking tax is lack and for hotel tax and groundwater tax reporting mechanism are alredy well underway.Keywords : contribution, reporting, hotel tax, groundwater tax